Colour preference and light sensitivity in trilobite larvae of mangrove horseshoe crab, Carcinoscopius rotundicauda(Latreille, 1802) - Srijaya, T.C.; Pradeep, P.J.; Hassan, A.; Chatterji, A.; Shaharom, F.; Jeffs, A. (2014)
The trilobite larvae of C. rotundicauda were tested to determine their colour preference and light sensitivity until their first moulting (25 days post hatching) under laboratory conditions. Maximum congregation size of the trilobite larvae was found in the white zone respectively where (n= 12) followed by yellow (n= 8) and orange (n= 8), which showed the larval preference for lighter zones. Morisita’s index calculation showed a clumped/aggregated distribution (yellow, blue, orange and white) and uniform/hyper dispersed distribution (green, red and black) for various colours tested. Trilobite larvae showed least preference for brighter regions while tested in the experiment [black; (n=4) and red; (n=5)]. Experiments done to determine the light sensitivity of trilobite larvae showed that the larvae had more preference towards ultraviolet lights. The maximum congregation size of 38.8 and 40.7% of the larvae was encountered under ultraviolet light, when the light sources were kept horizontal and vertical, respectively. Overall, results suggested that the trilobite larvae of C. rotundicauda, preferred light source of shorter wavelengths (UV light) and colours of lighter zone (white, yellow, orange), which might be due to their adaptation to their natural habitat for predator avoidance, prey selection and water quality.